Microbial community assembly and co-occurrence relationship in sediments of the river-dominated estuary and the adjacent shelf in the wet season. (1st September 2022) - Lu, Meiqing; Wang, Xuejing; Li, Hailong; Jiao, Jiu Jimmy; Luo, Xin; Luo, Manhua; Yu, Shengchao; Xiao, Kai; Li, Xiang; Qiu, Wenhui; Zheng, Chunmiao
Abstract: In the estuarine ecosystem, microbial community plays a vital role in controlling biogeochemical processes. However, there is currently limited comprehensive study on the deterministic and stochastic processes that drive the microbial community assembly in the estuaries and adjacent shelves. In this study, we systematically investigated the co-occurrence relationship and microbial community assembly in the sediments along a large river-dominated estuary to shelf in the northern South China Sea during the wet season. The sampling sites were divided into estuary, transection, and shelf sections based on their salinity values. The microbial co-occurrence networks, hierarchical partitioning-based canonical analysis, null model, neutral community model, and the Mantel test were used to investigate the community assembly. Results suggested that microbial community in the estuary section exhibited more interactions and a higher positive interaction ratio than those in the transition and shelf sections. Stochastic processes dominated community assembly in the study, with homogenizing dispersal contributing the most. The estuary exhibited a higher degree of heterogeneous selection than the transition and shelf sections, whereas homogeneous selection showed an opposite trend. Only the estuary section showed dispersal limitation and undominated processes. The river inflow and the resulting environmental heterogeneity were believed to be the key regulators of the community assembly in the studied area. Our study improved the understanding of how microbial community assembly in estuaries and adjacent shelves. Graphical abstract: Image 1 Highlights: Microbial network had greater and closer interactions in the estuary section. Stochasticity was more important than determinism in community assembly. Heterogeneous selection dropped from estuary to shelf. The Pearl River inflow and environmental heterogeneity shaped community assembly.